Development of Topological Mappings for Autonomous Agricultural Vehicles - Mehrolhassani, Moein (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Automation system of agricultural crop plantation requires many subsystems such as low level tracking, path planning, obstacle detection, manoeuvres at the path terminations, etc. This study proposes semantic annotation for the information flow between the automation subsystems, filling the gap between the planning and implementation of crop production by developing two missing subunits: determination of obstacles that may threaten agricultural vehicles using the satellite images of target field, and determination of proper path for the agricultural vehicles to process rows of crops. For the attributes of obstacles, semantic annotation on the map of target field is preferred using Resource Description Framework/Extensible Mark-up Language (RDF/XML) in order to be exchangeable and reusable with other stages, systems, devices and applications. Developed Matlab code determines the target field by a GPS coordinate inside the field. An interactive initialization stage provides download of the satellite images from Google Maps API for determination of the field boundaries. The code for detection and positioning of the circular shaped obstacles are using Prewitt, Sobel, Roberts, and Canny edge detection, and Hough transformation algorithms. The developed method is tested on 51 target fields. It provides 45% improvement in detection error rate compared to raw application of the algorithms. Keywords: Image processing, Obstacle detection, Path planning, Semantic annotation, RDF/XML mapping.

ÖZ: Tarımsal tahıl üretimi otomasyon sistemlerinde alt düzey iz takibi, yol planlaması, engel tayini, yol sonunda manevra gibi birçok alt sistem gerekir. Bu çalışma, tarımsal otomasyonu gerçekleştirmede gereken tarım aracına tehdit olabilecek engelleri uydu görüntüsünden tanıma ve araçların ürün sıralarını işlemesine uygun yol planlama alt sistemleri arasındaki bilgi akışının semantik işaretleme yoluyla çözülmesi önerilmektedir. Engellerin özellikleri hedef tarlanın haritasına RDF/XML kullanarak semantik işaretleme yöntemiyle kaydedilmekte, böylece birimler arasında verimli bilgi akışı sağlanmaktadır. Bilginin başka sistem, araç, ve uygulamalar için dönüştürülebilir ve tekrar kullanılabilirliği için semantik işaretlemede RDF/XML tercih edilmiştir. Geliştirilen Matlab kodu tarlayı içindeki her hangi bir GPS koordinatından belirlemektedir. Google Maps API kullanarak indirilen uydu görüntüsünde tarla sınırları etkileşimli giriş aşamasıyla belirlenmektedir. Çembersi biçimleri bulmak ve yerini belirlemek üzere Prewitt, Sobel, Roberts, ve Canny kenar belirleme ile Hough dönüşümü kullanılmaktadır. Geliştirilen yöntem 51 hedef tarla üzerinde sınanmıştır. Geliştirilen yöntem, kenar bulma ve Hough dönüşümlerinin ham kullanımına göre engel bulma hatasını %45 düşürmüştür. Anahtar Sözcükler: Görüntü işleme, Engel bulma, Yol planlama, Semantik işaretleme, RDF/XML haritalama.
Doctor of Philosophy in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2016. Supervisor: Assist. Prof. Dr. Mehmet Bodur.
Keywords: Computer Engineering; Computer Vision - Image and Object Recognition; Automation Systems - Agriculture; Image processing; Obstacle detection; Path planning; Semantic annotation; RDF/XML mapping